1976
DOI: 10.1017/s0033291700015841
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of plasma chlorpromazine levels I. Plasma levels of the drug, some of its metabolites and prolactin during acute treatment

Abstract: SynopsisSeventeen acute psychotic patients were studied in the course of chlorpromazine (CPZ) treatment. Blood samples were taken weekly both before and two hours after the morning CPZ dose. Plasma levels of CPZ, CPZ sulphoxide (CPZSO) monodesmethylated CPZ (NOR1CPZ) and 7-hydroxy CPZ (7OH CPZ) were estimated by gas chromatography. Plasma prolactin, luteinizing hormone, testosterone and oestrogens were measured by radioimmunoassay. Six of the seven patients who showed no clinical improvement had plasma CPZ lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

1978
1978
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(21 citation statements)
references
References 18 publications
2
18
1
Order By: Relevance
“…Mackay (197S) points out that in this study it is not clear whether the patients were treated long term or for only a short time, and suggests that if the latter was the case then 7 -hydroxy chlorpromazine may not have reached measurable quantities in the plasma. However, Wiles et al (1976) and Kolakowska et al (1976) using a similar technique to that of Mackay were not able to detect 7-hydroxychlorpromazine in all patients, many of whom were chronic schizophrenics receiving long term phenothiazine treatment (see section 3.1.2). Phillipson et al (1977) utilised the technique of Mackay et al (1974) and was able to quantify 7-hydroxychlorpromazine in all 9 patients studied.…”
Section: Analytical Problems: Quantitation Of 7 -Hydroxychlorpromazinmentioning
confidence: 93%
See 1 more Smart Citation
“…Mackay (197S) points out that in this study it is not clear whether the patients were treated long term or for only a short time, and suggests that if the latter was the case then 7 -hydroxy chlorpromazine may not have reached measurable quantities in the plasma. However, Wiles et al (1976) and Kolakowska et al (1976) using a similar technique to that of Mackay were not able to detect 7-hydroxychlorpromazine in all patients, many of whom were chronic schizophrenics receiving long term phenothiazine treatment (see section 3.1.2). Phillipson et al (1977) utilised the technique of Mackay et al (1974) and was able to quantify 7-hydroxychlorpromazine in all 9 patients studied.…”
Section: Analytical Problems: Quantitation Of 7 -Hydroxychlorpromazinmentioning
confidence: 93%
“…These investigators suggested then that the subsequent decline in plasma levels of chlorpromazine, despite a fixed dose, was the result of enzyme induction. Wiles et al (1976) studied 17 acute psychotic patients receiving a course of chlorpromazine treatment. Blood samples were collected immediately prior to the morning dose (0 hour) and again 2 hours later.…”
Section: Role Of Chlorpromazine Metabolites In Therapeutic Responsementioning
confidence: 99%
“…46). During acute neuroleptic treatment, the plasma Prl level has been found to be significantly correlated with the serum levels of neuroleptics (31,51,54), but only within a narrow range as there is a maximal Prl response at low doses of neuroleptics, below the therapeutic range (22,34). Another significant correlation between the potency to release Prl and their antipsycho tic property has been reported (22,33).…”
Section: Introductionmentioning
confidence: 99%
“…Assessments of psychiatric state was made using the Brief Psychiatric Rating Scale (BPRS, Overall and Gorham 1962), with the modified glossary employed by Wiles et al (1976) where the item for disorientation item is replaced by an item for elation.…”
Section: Subjectsmentioning
confidence: 99%